A PLAN FOR MANPOWER DEMAND IN LIBYA - الانصاری د.على رفاعه (Dirasat in Economics and Business, 1969)
Where is the truth about manpower in Libya ? îs it true that there en deficit? Is it real that there is unemployment? or even underemploy ment? Do we leave the door open for labour influx from the other Arab countries or have we to close the door ? Each cry takes refuge in some sort of statistics. So where is the truth ? The article under the same title in the Arabic section deals with this problem and tries to find out the true picture and assumes a certain plan. Now that the Libyan revolution has adopted socialism as a political ideology, a revision of previous plans is intended to call upon a scientific contribtion to the problem. The articls comprises four sections. Sources of supply of labour. 2. A quantitative analysis of the existing labour force. 3. An estimation of the labour demand for the next five years. 4. Available facilities of training. Professor of Business Department, Faculty of Economics, Benghazi AND BUSINESS REVIEW THE LIBYAN ECONOMIC AND BUS Then we come to conclusions. As for the sources of supply we find that the no runs at an annual rate of 3.65% with an anticipation 1974. Since the effective manpower in Libya is estimate of the total population, this will add an approximate numh to the existing force which runs around 439000 in 19 phenomenon worth noting is the unbalanced distribution ation as two thirds concentrate in the Western provinces of + while the Eastern provinces get 29% for the Southern ones the population growih ticipation of 2,214,000 stimated to be 25.997 number of 105.000 in 1968. Another tribution of popul. nces of the country Nomads economy Settlement is another important factor to be considered. N. and semị - nomads are not truly contributing to the modern en of the country. Their participation needs a long course of rehabilita and resettỊement. Only 259,000 households out of 331.990 considered settled and depended upon in developing the modern Libyan economy. Another striking feature is the great numbers out of the labour force. The natives in labour force amount to 388,000 out of 1,182,000 of age groups more than 6 years old. The percentage is 32.5 which means than 67.5% are economically not active. It is a low proportion in comparison with other nations. The corresponding proportion is 37% in U. A. R. and 42% in U. S. A. The main reason, according to statistics, is due to the refrain of the Libyan women from sharing public life because of prevailing traditions, The analysis of the present labour force showed that the percentage of male labourers is satisfactory while it is far lagging behind in the female sectors of different age groups. As for the unemployed seekers for work, they amount to 29,00, in the age groups between 15 and 65 years. This figure cannot be sa to be stable because of the quick labour turnover in the private ente prise sector. It is contradictory to have an unemployment prob ABSTRACTS 93 a deficit of labour is acutely felt. In our assume g supply for the badly needed demand. the time when a defin it is the wrong supply to There is a broad base in the successive o education remain Underemployment is clear in three fiel in interacts with labour both positively and passively ud base in the elemeniary stage which narrows sharply cessive preparatory and secondary stages. The vocational romains stagnafit and petrified in rigid frames. Jaument is also apparent in different sectors. It is peculiarly Three fields of economic activities, i.e. agriculture, services, classified. Workers in agricultural activiteis have been shrink in number during the past decade because of the petroleum boom. with the introduction of modern technology, agricultural growth tinued, though with decreasing contribution to GDP. Agricultural manpower acts as a reservior of supply for other urban sectors. and i When we come to the projected needs of labour, it is estimated to be around 160,000 persons. There is a clear deficiency in the highly educated technicians as well as in the skilled labour. Thus, the problem is not of quantity but of quality. The only solution lies in training. The available training facil. ities are inadequate with their present capacity of about 2,000 a year in all the diveresified fields. If we are supposed to meet demand we have to plan for 40 thousands a year. Thus training with a philosophy, policy, programs and resources both financial and human, is the only remedy for ihis bottleneck of economic development. In the decade of the Seventies, the only viable strategy for Libya, with its vast resources and scanty population is to aim towards the adoption of the concept of the modern state, deepening capital, raising productivity, through training, education and applied technology.